Sex and dominance: How to assess and interpret intersexual dominance relationships in mammalian societies - Kappeler, Peter M.; Huchard, Elise; Baniel, Alice; Canteloup, Charlotte; Charpentier, Marie J. E.; Cheng, Leveda; Davidian, Eve; Duboscq, Julie; Fichtel, Claudia; Hemelrijk, Charlotte K.; Höner, Oliver P.; Koren, Lee; et al. (Frontiers in Ecology and Evolution, 2022)
The causes and consequences of being in a particular dominance position have been illuminated in various animal species, and new methods to assess dominance relationships and to describe the structure of dominance hierarchies have been developed in recent years. Most research has focused on same-sex relationships, however, so that intersexual dominance relationships and hierarchies including both sexes have remained much less studied. In particular, different methods continue to be employed to rank males and females along a dominance hierarchy, and sex biases in dominance are still widely regarded as simple byproducts of sexual size dimorphism. However, males and females regularly compete over similar resources when living in the same group, and sexual conflict takes a variety of forms across societies. These processes affect the fitness of both sexes, and are mitigated by intersexual hierarchies. In this study, we draw on data from free-ranging populations of nine species of mammals that vary in the degree to which members of one sex dominate members of the other sex to explore the consequences of using different criteria and procedures for describing intra- and intersexual dominance relationships in these societies. Our analyses confirmed a continuum in patterns of intersexual dominance, from strictly male-dominated species to strictly female-dominated species. All indices of the degree of female dominance were well correlated with each other. The rank order among same-sex individuals was highly correlated between the intra- and intersexual hierarchies, and such correlation was not affected by the degree of female dominance. The relative prevalence of aggression and submission was sensitive to variation in the degree of female dominance across species, with more submissive signals and fewer aggressive acts being used in societies where female dominance prevails. Thus, this study provides important insights and key methodological tools to study intersexual dominance relationships in mammals.